2015
DOI: 10.1111/dote.12388
|View full text |Cite
|
Sign up to set email alerts
|

Association between the thoroughness of the histopathological examination and survival in patients with esophageal squamous cell carcinoma who achieve pathological complete response after chemoradiotherapy

Abstract: The College of American Pathologists guidelines recommend examining at least four representative tumor blocks for determining pathological T stage in patients with primarily resected esophageal cancer. Whether the same pathological requirements are adequate in patients undergoing esophagectomy following neoadjuvant chemoradiotherapy (nCRT) remains unclear. We hypothesized that current examination protocols may underestimate the presence of microscopical residual disease after nCRT, potentially leading to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the present study, we evaluated RCV by examining whole stepwise sections, including non-cancerous region, for the purpose of determining the optimal cutoff values. Even though the previous studies recommended that the histopathological evaluation of preoperative treatment required the meticulous examination by a larger number of tissue sections than that for primarily resected esophagus, 9,21 the RCV evaluation in whole stepwise sections may present a very troublesome task in routine clinical practice. However, because the cutoff value of RCV (1.0 cm 3 ) was very small in comparison with the range of RCV (0-49.3 cm 3 ), we believe that the residual cancer measurement by the whole stepwise examination is unnecessary for macroscopically huge cancers in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we evaluated RCV by examining whole stepwise sections, including non-cancerous region, for the purpose of determining the optimal cutoff values. Even though the previous studies recommended that the histopathological evaluation of preoperative treatment required the meticulous examination by a larger number of tissue sections than that for primarily resected esophagus, 9,21 the RCV evaluation in whole stepwise sections may present a very troublesome task in routine clinical practice. However, because the cutoff value of RCV (1.0 cm 3 ) was very small in comparison with the range of RCV (0-49.3 cm 3 ), we believe that the residual cancer measurement by the whole stepwise examination is unnecessary for macroscopically huge cancers in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For stage II or III localized thoracic ESCC, the recent meta-analysis showed that preoperative concurrent chemoradiotherapy followed by surgery reduces locoregional recurrence and has significant survival benefit compared to surgery alone [ 16 ]. The achievement of a pathological complete response is commonly considered an important prognostic factor after preoperative chemoradiation [ 17 ]. Until now, there is no clear prognostic factor to predict treatment response of preoperative chemoradiation.…”
Section: Discussionmentioning
confidence: 99%